1992
DOI: 10.1080/01652176.1992.9694327
|View full text |Cite
|
Sign up to set email alerts
|

Preselection of finishing pigs on the farm as an aid for meat inspection

Abstract: SUMMARYThe ability of pig suppliers to separate pigs with abnormalities from pigs without abnormalities at the end of the finishing period was investigated Nineteen hundred and seventy-eight pigs, delivered by 22 pig suppliers, were involved in the experiment The pigs were inspected on the farm by the pig supplier and separately, by a veterinary expert The animals were sent in 22 deliveries to one slaughterhouse. A veterinary meat inspector carried out the ante-and post-mortem inspections. The results of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
24
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 3 publications
6
24
0
Order By: Relevance
“…Work has been undertaken, in several countries, to evaluate the use of farm-level health information for meat inspection purposes. In the Netherlands (Snijders et al, 1989;Harbers et al, 1992a), a study was conducted evaluating the utility of Quality Information Cards (QUIC; capturing data on health and drug use problems) accompanying shipments of pigs to slaughter. Their value was relatively limited, with a low predictive value for abnormalities such as arthritis, liver condemnation and lung lesions.…”
Section: 343mentioning
confidence: 99%
“…Work has been undertaken, in several countries, to evaluate the use of farm-level health information for meat inspection purposes. In the Netherlands (Snijders et al, 1989;Harbers et al, 1992a), a study was conducted evaluating the utility of Quality Information Cards (QUIC; capturing data on health and drug use problems) accompanying shipments of pigs to slaughter. Their value was relatively limited, with a low predictive value for abnormalities such as arthritis, liver condemnation and lung lesions.…”
Section: 343mentioning
confidence: 99%
“…2,14 If the stress of disease or injury in suspects increases faecal shedding, then this could be increasing the risk of contamination of hides and subsequently meat with microbial hazards. 15 Harbers et al 16 demonstrated that there were more gross abnormalities in pigs classified as suspects than in normal pigs and, without any training, producers were able to find more suspects than abattoir antemortem inspectors. If abattoir antemortem inspection were enhanced by the addition of producer-conducted antemortem inspection on-farm, then the removal or segregation of high-risk stock is likely to be improved.…”
mentioning
confidence: 99%
“…If abattoir antemortem inspection were enhanced by the addition of producer-conducted antemortem inspection on-farm, then the removal or segregation of high-risk stock is likely to be improved. 2,16 Benefits could include reduced likelihood of cross-contamination of other pigs by cleaning in-contact surfaces and equipment before resuming the slaughter of apparently healthy pigs. Improved slaughter chain efficiencies are possible by scheduling extra inspectors and skilled trimmers during the processing of suspect pigs to maintain normal chain speed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Denmark 'traditional' and 'visual' meat inspection systems, were compared by Mousing et al (13) and Willeberg et al using data from 183, 383 slaughter pigs (14,15). In the Netherlands the group of Harbers et al investigated the interrelationship between data from the farm of origin and the results of meat inspection (5,6,8,10) and the technique of inspection (5,7,9).…”
Section: Introductionmentioning
confidence: 99%